Andrographolide, a natural anti-inflammatory agent: An Update - Li, Xiaohong; Yuan, Weichen; Wu, Jibiao; Zhen, Jianhua; Sun, Qihui; Yu, Minmin (Frontiers in Pharmacology, 2022)
Botanicals have attracted much attention in the field of anti-inflammatory due to their good pharmacological activity and efficacy. Andrographis paniculata is a natural plant ingredient that is widely used around the world. Andrographolide is the main active ingredient derived from Andrographis paniculata, which has a good effect on the treatment of inflammatory diseases. This article reviews the application, anti-inflammatory mechanism and molecular targets of andrographolide in different inflammatory diseases, including respiratory, digestive, immune, nervous, cardiovascular, skeletal and tumor system diseases. And describe its toxicity and explain its safety. Studies have shown that andrographolide can be used to treat inflammatory lesions of various systemic diseases. In particular, it acts on many inflammation-related signalling pathways. The future direction of andrographolide research is also introduced, as is the recent research that indicates its potential clinical application as an anti-inflammatory agent.